Effects of polysaccharide from Pueraria lobata on gut microbiota in mice - Chen, Rong; Liu, Bo; Wang, Xiaoyang; Chen, Kai; Zhang, Keyu; Zhang, Lifang; Fei, Chenzhong; Wang, Chunmei; Liu, Yingchun; Xue, Feiqun; Gu, Feng; Wang, Mi (International journal of biological macromolecules, 2020)
Polysaccharide was derived from Pueraria lobata (PPL) which was considered as one of the traditional Chinese medicinal and edible herbs. In the present study, PPL was administered in equal doses (12.5 mg/kg) to both normal mice and antibiotic-associated diarrhea (AAD) mice for two weeks, and was evaluated in terms of body weight, organ indices, gut structure, gut microbiota and short chain fatty acids. The results showed that normal mice treated with PPL not only reduced the isovaleric acid concentration (P < 0.05), but also significantly increased the abundance of beneficial bacteria, involving Oscillospira and Anaerotruncus (P < 0.05). In addition, PPL could relieve colonic pathological changes and gut microbiota dysbiosis caused by AAD. It indicated that PPL was a potential functional food ingredient by modulating gut microbiota.